Chapter 5 Verb Agreement Theoretical perspectives - Quer, Josep (Taylor & Francis, 2021)
This chapter discusses the scholarship that takes this type of argument encoding as grammatical agreement, and presents the formal analyses proposed and the arguments made to defend its linguistic nature by opposition to a gestural one. It properties associated with it will be described and exemplified. Agreement auxiliaries feature in the first analyses of agreement because ASL have one, but research has shown that they are not rare across sign languages. Quite significantly, agreement auxiliaries co-occur with plain verbs, many of which have transfer or motion semantics. Engberg-Pedersen also questions that cases like are instances of agreement proper and proposes instead that they are examples of pragmatic agreement, whereby the relation between the predicate and its argument is specified and in particular it occurs when contrast is at play. The complexities that agreement by itself raises in both sign and spoken languages but help better understand its properties and the range of variation of its instantiations vis-+a-vis related phenomena.